2022
DOI: 10.1042/cs20210989
|View full text |Cite
|
Sign up to set email alerts
|

Placental trophoblast-specific overexpression of chemerin induces preeclampsia-like symptoms

Abstract: Maternal circulating levels of the adipokine chemerin are elevated in preeclampsia, but its origin and contribution to preeclampsia remain unknown. We therefore studied 1) placental chemerin expression and release in human pregnancy, and 2) the consequences of chemerin overexpression via lentivirus-mediated trophoblast-specific gene manipulation in both mice and immortalized human trophoblast. Placental chemerin expression and release were increased in women with preeclampsia, and their circulating chemerin le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 38 publications
2
45
0
Order By: Relevance
“…Patients suffering from hypertension and PE showed significantly higher serum chemerin concentrations ( Cetin et al, 2017 ; Xie and Liu, 2022 ). The increased placental chemerin was also found in the villi of preeclamptic women ( Xu et al, 2014 ; Tan et al, 2022 ). Our findings demonstrated that Cmklr1 knockout mice had more invaded trophoblasts and larger arteries in the decidua and myometrium than those in wildtype mice.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Patients suffering from hypertension and PE showed significantly higher serum chemerin concentrations ( Cetin et al, 2017 ; Xie and Liu, 2022 ). The increased placental chemerin was also found in the villi of preeclamptic women ( Xu et al, 2014 ; Tan et al, 2022 ). Our findings demonstrated that Cmklr1 knockout mice had more invaded trophoblasts and larger arteries in the decidua and myometrium than those in wildtype mice.…”
Section: Discussionmentioning
confidence: 82%
“…Our findings demonstrated that Cmklr1 knockout mice had more invaded trophoblasts and larger arteries in the decidua and myometrium than those in wildtype mice. Consistently, overexpression of trophoblastic chemerin diminishes trophoblast invasion ( Tan et al, 2022 ). These observations indicate that CMKLR1 mediates the role of chemerin in pregnancy.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Recent reports confirmed the role of CHEM in the pathogenesis of preeclampsia. Tan et al [ 75 ] indicated that placental CHEM expression and release increased in women with this disorder. It has been shown that CHEM reduced vascular endothelial factor-A and inhibited trophoblast migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that CHEM reduced vascular endothelial factor-A and inhibited trophoblast migration and invasion. Moreover, according to the same authors, trophoblast CHEM overexpression in mice contributed to fetal growth restriction [ 75 ]. In the present study, CHEM, by increasing the expression of TGFβ1 protein in the endometrium, may contribute to the inadequate activation of NK cells and the development of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%